The influence of transition speed on event outcomes in a high performance football team - Turner, B. J.; Sayers, M. G. L. (International Journal of Performance Analysis in Sport, 2010)
Research has suggested that fast counter-attacks (transitions) in Football influence the number of positive attacking outcomes. However, very few studies have analysed the transition as a whole and so the determinants of transition speed and how it is affected by other variables remains undefined. The aim of this study was to determine the relationships between transition speed, the various aspects that define a transition (e.g. passing characteristics, position on the field, etc.) and positive/non-positive outcomes during high level Football matches. Analysis was based on recording every transition during 27 Football matches played by a successful team during the 2009/2010 Hyundai A-League season (n=1105). Transition outcomes were assigned as either positive (Shot, Penalty, and Free kick), or non-positive (Tackled, Passed Out, Passed Back to GK, Offside, and Pass Intercepted). Significant differences were found between transition speed and transition starting field position (p < .001), pass sequence length (p < .001), and number of players involved (p < .001). No significant differences were found between mean transition speeds of positive and non-positive outcomes (p = .133). These results established that positive and non-positive outcomes occurred irrespective of how fast the team transitioned. However, performance indicators that formed part of the build-up play significantly affected transition speed and transition outcomes.